Bird Integumentary Melanins: Biosynthesis, Forms, Function and Evolution - Galván, Ismael (Int J Mol Sci, 2016)
Melanins are the ubiquitous pigments distributed in nature. They are one of the main pigments responsible for colors in living cells. Birds are among the most diverse animals regarding melanin-based coloration, especially in the plumage, although they also pigment bare parts of the integument. This review is devoted to the main characteristics of bird melanins, including updated views of the formation and nature of melanin granules, whose interest has been raised in the last years for inferring the color of extinct birds and non-avian theropod dinosaurs using resistant fossil feathers. The molecular structure of the two main types of melanin, eumelanin and pheomelanin, and the environmental and genetic factors that regulate avian melanogenesis are also presented, establishing the main relationship between them. Finally, the special functions of melanin in bird feathers are also discussed, emphasizing the aspects more closely related to these animals, such as honest signaling, and the factors that may drive the evolution of pheomelanin and pheomelanin-based color traits, an issue for which birds have been pioneer study models.